Vocational and higher education in Germany : the growth of overlaps and transition opportunities - Ertl, Hubert [Verfasser] (My University, 2022)
This contribution describes the role of vocational qualifications in Germany and shows the increasingly blurring boudaries between the two sub-systems vocational education and higher education. Special attention is given to the dual study programmes (duale Studiengänge) and their growing importance which is connected to the introduction of Bachelor degrees in Germany in the aftermath of the Bologna Declaration of 1999. In his concluding remarks, the author states that growing overlap between higher and vocational education poses risks as well as opportunities for both sectors. Crucial for the successful development of new education and training formats is in his view that this takes place "in collaboration rather than in a spirit of competition". (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; 370; Berufsausbildung; Hochschulbildung; Durchlässigkeit im Bildungssystem; Dualer Studiengang